Extra Hepatic Portal Venous Obstruction in Children: Approach and Management (Mediscope, 2019)
Portal hypertension in children is not uncommon and extra hepatic portal venous obstruction (EHPVO) constitute about 75% of portal hypertension. Several risk factors predispose to development of EHPVO such as neonatal sepsis, umbilical catheterization, severe dehydration, abdominal trauma or surgery etc. Common presentations are haematemesis and splenomegaly. Acute variceal bleeding is a medical emergency. Liver function is normal in extrahepatic portal hypertension unless there is portal bilopathy. High index of suspicion is the key of early diagnosis. Esophagogastrodudenoscopy is diagnostic for portal hypertension and doppler ultrasonography of portal vein confirm extra hepatic portal venous obstruction (EHPVO) in presence of thrombus and/or cavernoma. Adequate management including endotherapy, pharmacotherapy and/or surgery is an important key for better outcome.Mediscope Vol. 6, No. 2: Jul 2019, Page 79-85